A Study on the Spatiotemporal Characteristics of the Xi’an Metropolitan Area Based on the Coupling and Coordination of Ecosystem Services and Human Well-Being - Gao, Yunsong; Zhang, Pei; Xu, Yuqian; Li, Zhijun; Liu, Kaixi (Land (Basel), 2025)
The escalating conflict between ecosystem degradation and the rising demands of humanity has rendered the attainment of a scientific balance between ecosystem services and human well-being a critical concern in research on human–environment coupling and sustainable development. Metropolitan areas are pivotal in long-term sustainable development strategies and regional equity due to rapid urbanization and the tension between ecosystem degradation and human well-being. This study proposes a novel perspective, transitioning from a “cascade” to a “coupling” approach in examining the relationship between ecosystem services and human well-being. Taking the Xi’an metropolitan area as the research subject, the research employs a coupling coordination degree model to analyze the spatiotemporal characteristics of their relationship across multiple scales. The key findings of the paper are as follows: (1) We found a severe shrinkage in the ecosystem service value (2000–2020). The ecosystem services in the Xi’an metropolitan area were significantly compromised under the pressure of homogenized human well-being improvement, resulting in weak coupling and coordination between the two. (2) There was a spatial imbalance between supply and demand. Ecosystem service values displayed a core-to-periphery increasing spatial pattern, while human well-being levels exhibited a core-to-periphery decreasing distribution, indicating a marked spatial mismatch. (3) Diverse coupling dynamics within the region were identified. Driven by factors such as the resource distribution, land use, scale effects, and benefit allocation, the coupling relationships between ecosystem services and human well-being varied across development stages and contexts. Ecosystem services functioned as either flexible facilitators or constraints on human well-being improvement. This research provides a blueprint for sustainable development, offering a framework to balance urban growth with ecological health while ensuring equitable well-being across the Xi’an metropolitan area. The study highlights the need for strict ecological space protection, enhanced urban development quality, and integrated human–environment system management. Efforts should focus on minimizing land use trade-offs and spatial competition, strengthening spatial synergy in supply–demand coupling, and promoting sustainable regional development.